IMPLEMENTASI PENINGKATAN PARIWISATA BAHARI BERADASARKAN PERATURAN BUPATI KABUPATEN PESAWARAN NOMER 35 TAHUN 2017 TENTANG PENGELOLAAN KAWASAN WISATA BAHARI DI KABUPATEN PESAWARAN - Ahmad Ulya (Law Department Jenderal Achmad Yani University, 2022)
One of the forms of tourism in Indonesia is marine tourism. The marine area is afavorite place for both local and international tourists to visit and enjoy the naturalbeauty of the sea. In general, marine areas are located on the coast and are locatedin places that have a natural, cool and healthy environment so that they can achievean optimal recreational activity. Pesawaran Regency is one of the regencies inLampung Province. Pesawaran Regency most of the tourist attractions are still notdeveloped and there are no adequate facilities. In the context of structuring marinetourism areas in Pesawaran Regency in order to increase economic growth andpeople's welfare, environmental conservation and natural cultural resources, marinetourism in Pesawaran Regency needs to be managed properly. There are efforts inorder to improve the tourism sector in Pesawaran Regency, one of these efforts isthe issuance. Regulation of the Regent of Pesawaran Regency Number 35 of 2017concerning Management of Marine Tourism Areas in Pesawaran Regency. With thisregulation, it is hoped that tourism in Pesawaran Regency can become a touristdestination.